Increasing the shelf life of tomato fruits using physical, chemical and genetic modification methods - Murodov, A A; Abdurakhmonov, I Y; Buriev, Z T; Kushakov, S O; Kamalova, L K; Bashirxonov, Z H; Yusupov, A N; Mamajonov, B O; Obidov, N S H; Ayubov, M S (Plant Science Today, 2025)
The tomato is one of the most consumed vegetables and is rich in numerous beneficial and nutritious compounds. As climacteric fruits, tomatoes undergo significant metabolic changes during their growth and ripening. During fruit ripening, irreversible changes occur in the color, taste and appearance of the fruit. Shortly after ripening, the fruit begins to lose its shape and structural integrity. Approximately 50% of ripe tomatoes do not reach consumers. The primary cause of this loss is excessive fruit softening, which compromises the integrity of tomatoes during harvesting and transportation, making them susceptible to fungal and bacterial infections. Generally, fruit softening results from increased enzymatic activity that breaks down the fruit cell wall. Currently, chemical, physical and biotechnological methods are employed to extend tomato shelf life. These methods help reduce or inhibit the enzymatic activity responsible for fruit softening. The review provides a concise overview of these preservation methods. We focus on enhancing fruit preservation through plant genome modifications using modern biotechnological techniques, such as RNA interference (RNAi) and CRISPR/Cas9. Additionally, we will briefly discuss the advantages and limitations of these genetic engineering approaches.